Indonesian Fisheries Policy Reform: Compliance with Stringent Food Safety Requirement Of Importing Countries - Fauna Alwy (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
The main objective of this research is to discover the idea of innovation of Indonesia's legislation system on food security/seafood which has been heavily influenced by trade relations between Indonesia and the European Union as a group of major importing countries. This is a case study that largely examines and presents trade disputes between Indonesia and some major importing countries, especially with the EU countries as a major group of country importers of fishery products and seafood from Indonesia. The various disputes and complaints found in this case study demonstrate the fact that the marine fisheries sector as one of Indonesia's mainstay sectors has a very potential economic value for the country's foreign exchange earnings. There is a very close relationship between the fisheries sector with the fulfillment of people's living needs as well as the development of the economic sector in general, including food safety aspects. This should be addressed appropriately and efficiently by the government by adjusting and even updating laws and regulations in this sector by the international food standard/food security; given the numerous demands and rejection of most of Indonesia's trading partner countries in this sector. Keyword: Indonesian Fisheries, Policy Reform, Compliance, Food Safety Requirements, Importing Countries.